The Influence of Consumer Confidence, Service Quality, and Product Differentiation Factors on the Success of Online Service Platforms: Case Studies on Online Transportation Platforms in Sukabumi City - Sudirjo, Frans; A., Chevy Herli Sumerli; Mardikawati, Budi; Judijanto, Loso (West Science Journal Economic and Entrepreneurship, 2023)
This study investigates the complex dynamics that shape the success of online service platforms in Sukabumi City through quantitative analysis using Structural Equation Modeling with Partial Least Squares (SEM-PLS). Focusing on the interactions between Consumer Trust, Product Differentiation, Service Quality, and Online Service Platform Success, this study took a sample of 245 participants. The measurement model underlined the reliability and validity of the constructs, while the structural model explained the significant relationships. Notably, Consumer Trust and Product Differentiation emerged as strong predictors of platform success. This study contributes nuanced insights for platform operators and policy makers seeking to optimize online service platforms in the specific context of Sukabumi City.